Investigation on electrical, thermal and mechanical properties of thermally aged pressboard impregnated with mixed mineral oil and synthetic ester fluid. Issue 10 (19th February 2021) - Somasundaram Karthikeyan, Amizhtan; Mahidhar, Gorla Durga Pawan; Sarathi, Ramanujam; Taylor, Nathaniel; Edin, Hans
Abstract : The proposed study compares the electrical, thermal and mechanical performances of thermally aged cellulose pressboard material impregnated in mineral oil, synthetic ester fluid and mixed oil. The electrical insulation characteristics of oil‐impregnated pressboard (OIP) are studied by means of surface discharge inception voltage (SDIV) using an ultra‐high frequency technique and surface potential measurement analysis. It indicates that OIP aged in mineral oil has higher surface potential due to higher charge trap density compared to that of the mixed oil and synthetic ester fluid. Mechanical and thermal characteristics of the aged OIP are studied by means of tensile strength measurement and thermo‐gravimetric analysis, respectively. The change in the chemical composition of OIP is studied by means of laser‐induced breakdown spectroscopy, which indicates lower plasma temperature with mineral oil‐based OIP indicating higher degradation state. To further understand the microscopic structure of the thermally aged OIP in different oils, scanning electron microscopy and X‐ray diffraction studies have been performed. The pressboard thermally aged in synthetic ester fluid and the mixed oil has better electrical, thermal and mechanical properties as compared with the pressboard aged in mineral oil.